Wybrane techniki WAS w wyodrębnianiu i profilowaniu segmentów rynku dóbr trwałego użytku - Dziechciarz, Marta (The Application of Multivariate Techniques to Identify and Profile Segments in Consumer Durables Market, 2009)
The paper is a theoretical and practical discussion on possibilities of enhancement of the market segmentation procedure in the consumer durables market. The problem of using multivariate techniques in order to find and describe homogenous market segments is of great importance, mainly because of the complexity of the matter. In order to identify homogenous groups of costumers, the CHAID algorithm was used. Multivariate correspondence analysis was tested as a profiling tool. The proposed two step procedure provided excellent potential to better understand decisions of durable customers. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 265-273